2016
DOI: 10.1063/1.4953679
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of biological cells at cellular level and correlation with disease state

Abstract: This paper reports the thermal conductivity k of matched pair cell lines: two pairs of a normal and a cancer cell, one pair of a primary and metastatic cell. The 3ω method with a nanoscale thermal sensor was used to measure k at the single-cell level. To observe the difference in k between normal and cancer cells, the measurements were conducted for Hs 578Bst/Hs 578 T (human breast cells) and TE 353.Sk/TE 354.T (human skin cells). Then k of WM-115/WM-266-4, a primary and metastatic pair of human skin cell, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…The measured thermal conductivity of the different cell lines were slightly less than that of water (κ = 0.63 W mK −1 at 37 °C), which is consistent with the fact that water normally accounts for ≈80% of the cell's weight . Furthermore, the water content within living cells harbors a large composition of macromolecules, such as proteins, with calculated thermal conductivity less than water, thereby contributing to a lower thermal conductivity of living cells .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The measured thermal conductivity of the different cell lines were slightly less than that of water (κ = 0.63 W mK −1 at 37 °C), which is consistent with the fact that water normally accounts for ≈80% of the cell's weight . Furthermore, the water content within living cells harbors a large composition of macromolecules, such as proteins, with calculated thermal conductivity less than water, thereby contributing to a lower thermal conductivity of living cells .…”
Section: Resultssupporting
confidence: 69%
“…Since cellular response to overheating is diverse, ranging from improved diffusion rate across the cellular membrane to irreversible damage and protein denaturation, several techniques were developed to measure cellular thermal‐transport properties. 3‐Omega and thermal lensing techniques were employed to measure thermal conductivity and diffusivity (and effusivity as well), respectively. The cellular thermal diffusivity however is not studied as a thermal indicator of different types of cancers or different sub‐types of the same cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The method relies on the difference in the thermal properties between the individual cells and the liquid medium they are growing in. This difference in thermal properties has been reported in previous studies [ 21 , 26 ]. More specifically, these studies have shown that the thermal conductivity ( ) of individual cells is lower than that of liquid culture media.…”
Section: Working Principlesupporting
confidence: 65%
“…A thermal-based cell proliferation assay can be done on the basis of heat generated by the metabolic activity of cells [ 23 , 24 , 25 ]. Analogous to EIS, a thermal read-out can also be based on the difference in thermal properties of individual cells and the liquid growth medium they reside in [ 26 ]. This principle is demonstrated by Reyes et al using a thermal read-out based on alternating current (AC) for monitoring biofilm formation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For applications at nanoscale, scanning thermal microscopy techniques use thermal probes attached to cantilevers that directly contact the material to detect nanoscale changes in heat flow 16 , from which thermal properties can be extracted. At microscale, the 3ω method has been used to measure the thermal conductivity of materials and single cells 17 , 18 . A number of microscopes have been developed that take advantage of the local change in refractive index upon chromophore absorption, some of which use vibrational spectroscopy to extract molecular content 15 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%